2012
DOI: 10.1007/s00709-011-0371-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth control by cell wall pectins

Abstract: Plant cell growth is controlled by the balance between turgor pressure and the extensibility of the cell wall. Several distinct classes of wall polysaccharides and their interactions contribute to the architecture and the emergent features of the wall. As a result, remarkable tensile strength is achieved without relinquishing extensibility. The control of growth and development does not only require a precisely regulated biosynthesis of cell wall components, but also constant remodeling and modification after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
138
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 65 publications
5
138
0
2
Order By: Relevance
“…2). It has been proposed that pectin plays an important role in both cell adhesion and cell separation in plant organ development (Micheli, 2001;Pelloux et al, 2007;Wolf and Greiner, 2012). We detected differences between wild type and kns4 both in the deposition of AGPs (Figs.…”
Section: Discussionmentioning
confidence: 67%
“…2). It has been proposed that pectin plays an important role in both cell adhesion and cell separation in plant organ development (Micheli, 2001;Pelloux et al, 2007;Wolf and Greiner, 2012). We detected differences between wild type and kns4 both in the deposition of AGPs (Figs.…”
Section: Discussionmentioning
confidence: 67%
“…The orientation of microfibrils is hypothesized to mechanically restrict the direction of cell extension, leading to anisotropic growth. Parallel cellulose microfibrils are separated during cell expansion (Marga et al, 2005), presumably yielding to internal turgor pressure and being loosened via the enzymatic modification of adjoining matrix polysaccharides (Wolf and Greiner, 2012;Cosgrove, 2016). Since microfibril diameters do not appear to decrease during the elongation process, the fibrils likely are not modified directly.…”
Section: Cellulose Visualization Of Crystalline Cellulose Microfibrilsmentioning
confidence: 99%
“…In cell walls and middle lamella, pectin can be modified by the enzyme pectin methylesterase (PME), which removes methyl groups by breaking ester bonds. The de-esterified pectin is able to form calcium-pectin cross-links, and thus stiffen the cell wall and reduce its expansion; see, e.g., [50]. On the other hand, mechanical stresses can break calcium-pectin crosslinks and hence increase the extensibility of plant cell walls and middle lamella.…”
mentioning
confidence: 99%
“…On the other hand, mechanical stresses can break calcium-pectin crosslinks and hence increase the extensibility of plant cell walls and middle lamella. It has been shown that chemical properties of pectin and the control of the density of calcium-pectin cross-links greatly influence the mechanical deformations of plant cell walls [34], and the interference with PME activity causes dramatic changes in growth behavior of plant tissues [50].…”
mentioning
confidence: 99%
See 1 more Smart Citation